Knowledge, attitudes, susceptibility and self-efficacy against HIV infection in adolescents from Cartagena, Colombia - Castillo Avila, Irma Yolanda; Ramirez Aguilar, Jennifer Paola; Silva Yepes, Karen Patricia; Caballero Pacheco, Maria Alejandra; Arrieta Yepes, Karen (Universidad y Salud, 2017)
Objective: To determine knowledge, attitudes, susceptibility and self-efficacy facing HIV infection in school adolescents in the city of Cartagena. Materials and methods: A descriptive cross-sectional study was made with a reference population of 15,686 adolescents from formal educational institutions who are enrolled in tenth and eleventh grades. A sample of 580 adolescents was estimated, and a probabilistic multi-stage sample was applied. The HIV/AIDS-65 Scale was used for data collection, previous informed consent. The data were processed using the Microsoft Excel program and were analyzed using descriptive statistics. Results: A total of 579 adolescents with an average age of 15.6 years (= 0.9 years), mainly of female sex (65.6% (380)) successfully completed the questionnaire. The 45% (261) presents deficient knowledge, 55% (318) presents misconceptions about the disease, 69.6% (400) showed negative attitudes, 46.1% (266) do not considered themselves susceptible to contract the disease and 49.5% (286) showed low self-efficacy for the prevention of the infection. Conclusion: Little knowledge about HIV and its modes of transmission, mixed with misconceptions, increases the likelihood of infection among adolescents, especially when negative attitudes, low perception of susceptibility and little self-efficacy for prevention are combined.